Проблемы исторической фонологии в работах М. И. Стеблин-Каменского - Воронкова, Г. В.; Кузьменко, Ю. К.; Степонавичюс, А. (Kalbotyra, 1985)
The article presents a survey of Professor Steblin-Kamenskij’s works and ideas on general and Germanic (especially Scandinavian) historical phonology.